Analysis of Factors Influencing the Quality of Local Government Financial Reports - Yunus Tulak Tandirerun; La Ode Hasiara; Noor Fachman Tjete; Mat Juri (International Journal of Artificial Intelligence Research, 2022)
This study intends to determine and analyze the influence and relationship: between information technology, internal control system, Parameters of Government Accounting, Quality of financial reports, information technology, System internal control, direct implementation of Government Accounting Standards, the indirect relationship of information technology, System control indirect relationship, indirect effect on the implementation of Government Accounting Standard through indirect effect on information technology. This study employs a quantitative approach based on Partial Least Squares (PLS). Examined from the perspective of the first equation, this study's findings reveal that organizational commitment, information technology, and internal control systems have direct and significant effects on the quality of financial reports. Implementing government accounting standards concurrently enhances the quality of financial reports. In contrast to the second equation, which indicates that organizational commitment and technology have a significant effect on good governance, control has a positive and insignificant effect on good governance, whereas accounting parameter implementation has a negative and insignificant effect on good governance. In addition, organizational commitment, the use of technology, and internal control have a significant impact on the quality of financial reporting, an indicator of effective governance. In contrast, the use of accounting principles has a positive and insignificant effect on excellent governance management through the quality of financial reporting